2021
DOI: 10.1101/2021.05.19.444787
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Starvation-induced cell fusion and heterokaryosis frequently escape imperfect allorecognition systems to enable parasexual interactions in an asexual fungal pathogen

Abstract: Asexual fungi include important pathogens of plants and other organisms, and their effective management requires understanding of their evolutionary dynamics. Genetic recombination is critical for species adaptability and could be achieved via heterokaryosis and the parasexual cycle in asexual fungi. Here, we investigate the extent and mechanisms of heterokaryosis in the asexual plant pathogen Verticillium dahliae. We used live-cell imaging and genetic complementation assays of tagged V. dahliae strains to ana… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
2
0

Year Published

2021
2021
2021
2021

Publication Types

Select...
1
1

Relationship

2
0

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 84 publications
1
2
0
Order By: Relevance
“…Conidial and hyphal fusion is an integral component of the establishment and development of fungal colonies [65], and nonself fusion could possibly grant access to parasexual generation of diversity [23,54]. We have previously demonstrated that NoxA is essential for CAT-mediated fusion of V. dahliae conidia or germlings [23], and we further found in the present study that the requirement for functional NoxA applies to both interacting cells.…”
Section: Discussionsupporting
confidence: 74%
See 2 more Smart Citations
“…Conidial and hyphal fusion is an integral component of the establishment and development of fungal colonies [65], and nonself fusion could possibly grant access to parasexual generation of diversity [23,54]. We have previously demonstrated that NoxA is essential for CAT-mediated fusion of V. dahliae conidia or germlings [23], and we further found in the present study that the requirement for functional NoxA applies to both interacting cells.…”
Section: Discussionsupporting
confidence: 74%
“…Fusion of vegetatively incompatible strains of fungi, including V. dahliae , usually triggers an incompatibility reaction that can cause cell death of the anastomosed compartments [54]. Based on the observations that this reaction in N. crassa is characterized by induction of ROS [57], and that genes involved in the OSR are up-regulated during CAT formation in Colletotrichum gloeosporioides [58], we used NBT staining to study O 2 •− accumulation in incompatible V. dahliae fusions (pairing Ls.17 H1-sgfp × 123V).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation